Using WhatsApp to support EFL reading comprehension skills with Turkish early secondary learners - Tumen Akyildiz, Secil; Celik, Vildan (Routledge Journals, Taylor & Francis Ltd, 2022)
The purpose of this study is to investigate the impact of reading tasks delivered through WhatsApp on students' achievements in English reading comprehension and explore students' views on the process. A mixed-method research model was used. The participants were 54 seventh grade students, aged 11-12, who were divided into experimental and control groups. Reading texts with comprehension questions were sent to the experimental group students' WhatsApp accounts. The tasks were designed to use all the facilities of WhatsApp. Finishing the reading comprehension activities over a set period of time, students sent their answers via WhatsApp to the teacher who returned the answer key to them. The control group students completed the same reading texts and activities in the classroom. The results showed that the experimental group performed better. It should be noted that the success of the WhatsApp group may be linked to the ranking and reward system which was implemented to encourage them. At the end of the study, students in the experimental group generally expressed their positive attitudes towards using WhatsApp to enhance their reading comprehension skills. We discuss the limitations and implications of this small-scale study for the further use of mobile technology to support language skills.
Keywords: WhatsApp; reading comprehension skills; mobile technology